Hukum Keluarga Islam Di Tunisia - Ratih Lusiana Bancin (Jurnal Penelitian Medan Agama, 2018)
The purpose of this study is to examine Islamic family law in Tunisia, which is considered unique because of the complexity of Tunisia. This study uses the library research and data collection is done by the method of documentation sourced from documents that are relevant to the problem collected. The analysis used is content analysis. The conclusion of this study is that the process of formulating and structuring Islamic family law in Tunisia is not only an attempt to codify the Maliki school of jurisprudence, but also takes progressive and revolutionary steps in an effort to legalize and administer the legal sector, especially Family Law. This is evidenced by the enactment of Tunisia's Code of Personal Status. From the historical point of view, the formation of the CPST was greatly influenced by France. Besides that, the Nationalists also have secular education background. Legal reforms carried out by the Tunisian government, in matters that exist do not intend to make deviations and abandon the principles of Islamic Law, but rather due to the government's desire to guarantee the welfare, peace and benefit of the people and people of Tunisia.